A comparative study on shared-use medicines in Tibetan and Chinese medicine - Ming-ming Zhao (Journal of Ethnobiology and Ethnomedicine, 2019)
Abstract Background Tibetan medicine (TM) and traditional Chinese medicine (TCM) are two independent traditional medical systems. Due to geographical factors, the development of Tibetan medicinal theory is relatively independent, but there are still many shared-use medicines in TM and TCM. However, a thorough and comparative study on those medicines is still absent. This study listed shared-use medicines by TM and TCM and analyzed the similarities and dissimilarities of these two medical systems. This paper also aimed to understand mutual influences like the shared history of TM and TCM and to roughly outline the exchanging process between them. Methods Shared-use medicines in TM and TCM were listed alphabetically. Information on the scientific name, material name, medicinal parts, and medical efficacy were extracted from publications. Shared-use medicines were grouped according to medicinal properties and medicinal parts used by TM and TCM. The historical origin and current status of clinical prescriptions of shared-use medicines were analyzed. Results A total of 136 shared-use medicines in TM and TCM were listed. Shared-use medicines that were used for a similar purpose in TM and TCM accounted for 14% of the total, while those used for different purposes accounted for 49% of the total, with some of the latter being commonly used in TCM. Shared-use medicinal herbs that originated from both Tibetan and Han regions accounted for 49% of the total, and those that were imported from South Asia and Southeast Asia were frequently observed in TM. Conclusion Owing to its unique geographical location and cultural diversity, the Tibetan region played a role as a development cradle for various traditional medicinal theories and knowledge. Medicinal knowledge was exchanged between TM and TCM during their parallel independent growth. Shared-use medicines in TM and TCM were mostly determined by flora similarity and medicinal trade, and they marked significant differences in their medicinal properties. However, medicines that were used for similar purposes in TM and TCM presented obvious commercial medicinal characteristic as well as the same chemical profile. The Tibetan region not only provided medicinal usage knowledge of TCM, but also served as a supply of medicinal resources attributing to “high altitude” locations.